2021
DOI: 10.3390/antibiotics10030243
|View full text |Cite
|
Sign up to set email alerts
|

Methicillin-Resistant Staphylococcus aureus Clonal Complex 398 as a Major MRSA Lineage in Dogs and Cats in Thailand

Abstract: The aim of this study was to present molecular and antimicrobial resistance characteristics of methicillin-resistant Staphylococcus aureus (MRSA) clonal complex (CC) 398 isolated from diseased dogs and cats in Thailand. A total of 20 MRSA isolates of 134 Staphylococcus aureus isolated from canine and feline clinical samples during 2017–2020 were CC398, consisting of sequence type (ST) 398 (18 isolates), ST5926 (1 isolate), and ST6563 (1 isolate) by multilocus sequence typing. spa t034 and staphylococcal casset… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…It has not yet been determined with certainty that this level of MRSA colonization is acquired by MRSA from pets [ 21 ]. Data from molecular typing studies show that veterinarians have infected small animals with a preponderance of related MRSA clones [ 122 ].…”
Section: Public Health Concernmentioning
confidence: 99%
“…It has not yet been determined with certainty that this level of MRSA colonization is acquired by MRSA from pets [ 21 ]. Data from molecular typing studies show that veterinarians have infected small animals with a preponderance of related MRSA clones [ 122 ].…”
Section: Public Health Concernmentioning
confidence: 99%
“…Ceballos et al [38] identified a new LA-MRSA lineage, the type (ST) 398 sequence that is in the CC398 grouping, which is now often found in livestock and domestic animals and infects humans. Thus, LA-MRSA-associated farm and domesticated animals with the CC398 clonal complex are starting to be widely reported globally [39], in horses [40], cattle [41], poultry [42], dogs [43], and cats [44].…”
Section: La-mrsamentioning
confidence: 99%
“…In 1989, LA-MRSA was first identified in a mare with metritis in Japan [10]. Since then, several investigators have identified the presence of LA-MRSA among horses in America, Europe, and Asia, with slight differences in the prevalence rates between regions [21,43,[45][46][47][48][49]. In several cases of LA-MRSA infection in horses, clones that differ from those found in normal livestock and domestic animals have been identified, namely, the CC8 clonal complex, which was previously associated with HA-MRSA infection in the hospital [21,47,48,50].…”
Section: La-mrsa In Horsementioning
confidence: 99%
“…CC22, CC30, CC5) and LA‐MRSA (e.g. CC398) clones have been widely reported (Aires‐de‐Sousa, 2017 ; Chueahiran et al, 2021 ; Gómez‐Sanz, Torres, Lozano, et al, 2013 ; Ma, Worthing, Gottlieb, et al, 2020 ; Quitoco et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%